BaliSpirit Festival as a Regenerative Event Transformation Model: The Tri Hita Karana Framework in Support of Sustainable Spiritual Tourism - dewi, Maha (Journal of Indonesian Tourism and Policy Studies, 2025)
The global tourism sector is undergoing a transition toward Regenerative Tourism (RT). RT emphasizes active ecosystem restoration and community empowerment, surpassing the objectives of passive sustainability. In Bali, this transition appears in the Trilogy of Serenity, Spirituality, and Sustainability. This study examines the BaliSpirit Festival (BSF) as a case study that operationalizes the local Tri Hita Karana (THK) philosophy. This philosophy integrates spiritual (Parhyangan), social (Pawongan), and environmental (Palemahan) harmony as its foundation. The study uses a descriptive-analytical qualitative methodology to evaluate BSF's practices in advancing Sustainable Spiritual Tourism (SST). Results show BSF has established a culturally grounded regenerative event model. Palemahan is implemented through rigorous closed-loop waste management and long-term restoration initiatives such as Bali ReGreen. These initiatives contribute to soil health improvement. Pawongan is reinforced through social equity and institutional legitimacy. A measurable social legacy is achieved via the Karma Outreach program, which supports multicultural health and education. THK provides a framework for authentic cultural sustainability Key Performance Indicators. This framework helps transform conventional Sustainable Event Management (SEM) into a regenerative model in which spiritual ethics (Parhyangan) underpin environmental stewardship. The BSF model serves as a pilot for Southeast Asian destinations to incorporate local values and achieve holistic sustainability. This model enhances the reputation of high-value, low-impact destinations.